Analysis of the radiation force of a Laguerre Gaussian vortex beam exerted on an uniaxial anisotropic sphere. (September 2015) - Qu, Tan; Wu, Zhen-Sen; Shang, Qing-Chao; Li, Zheng-Jun; Bai, Lu; Gong, Lei
Abstract: Based on the expansion of Hermite Gaussian (HG) beam in terms of spherical vector wave functions (SVWFs) utilizing Complex Source Point Method (CSPM) and the relation between HG beam and Laguerre Gaussian (LG) mode, we derived the expansion of LG vortex beam in terms of SVWFs. Using Generalized Lorenz Mie Theory (GLMT), the radiation force (RF) exerted on a uniaxial anisotropic sphere by a LG vortex beam with spiral phase distribution is calculated. The effects of the radial and azimuthal mode index of LG vortex beam, anisotropic permittivity tensor elements, and particle size on the dimensionless axial and transverse RF have been numerically analyzed in detail. Highlights: Radiation force on uniaxial anisotropic sphere by Laguerre Gaussian vortex beam is investigated. Analytical expression of Laguerre Gaussian vortex beam in terms of SVWFs is presented. Effects of the beam mode, permittivity on the radiation force are numerically analyzed.